Design of a Technician Attendance System for Internet Network Disturbances at PT Telkom Indonesia Using a Website - Ardiansyah, Fery; Irwan; Lubis, Akhyar (Cattleya Darmaya Fortuna, 2024)
Telkom Indonesia, or PT Telkom Indonesia (Persero) Tbk, is a telecommunications company based in Indonesia. Telkom Indonesia was founded in 1856 under the name